2014
DOI: 10.3329/cmoshmcj.v13i1.19410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Snakebite Cases Admitted in Dhaka Medical College Hospital

Abstract: Background: Snake bite is an important health hazard which may lead to fatality in rural areas of Bangladesh. An epidemiological study estimated the incidence of snake bite in Bangladesh about 8,000 per year with 22% mortality. In majority of cases the victims die before entrance to hospital because of their treatment seeking behavior from Ohzas. Present study is to see the clinical profile of snake bite cases admitted in Dhaka Medical College Hospital and also to find out problems in diagnosis and management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…dIscussIon This hospital based multi-centered study from the southern region of Nepal replicates findings from the past studies from Nepal which show that majority of the suicide attempts were done by individuals belonging to younger age group, female gender and are homemakers or students. [8][9][10][11][12] However, studies which conducted psychological autopsy of complete suicides registered in the police data, have always found more number of males compared to females. 13,14 In our study sample, many individuals belonged to indigenous or disadvantaged/minority communities, and this has also been highlighted in previous studies as well.…”
Section: Psychosocial and Personality Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…dIscussIon This hospital based multi-centered study from the southern region of Nepal replicates findings from the past studies from Nepal which show that majority of the suicide attempts were done by individuals belonging to younger age group, female gender and are homemakers or students. [8][9][10][11][12] However, studies which conducted psychological autopsy of complete suicides registered in the police data, have always found more number of males compared to females. 13,14 In our study sample, many individuals belonged to indigenous or disadvantaged/minority communities, and this has also been highlighted in previous studies as well.…”
Section: Psychosocial and Personality Factorsmentioning
confidence: 99%
“…In this study, self poisoning with pesticides, (mainly organophosphates) was found to be the most common method of suicide attempts similar to past studies of suicide attempt cases. [8][9][10][11][12] Contrary to this, hanging has been found to be the commonest method of mortality due to suicide in Nepal. 13,14 The discrepancy in the hospital based and police data could be because hanging cases have higher fatality and these individuals are less likely survive to reach the hospitals and are more likely to be reported to the police.…”
Section: Psychosocial and Personality Factorsmentioning
confidence: 99%
“…Quarrel as a significant risk factor was also noted in a study from Taiwan [41]. Recent studies, from both developing [42, 43] and developed countries [44, 45] also recognised increasingly that DSH is a common response to acute emotional distress.…”
Section: Discussionmentioning
confidence: 82%